The Land of Israel. Cross-Roads of Civilizations. Proceedings of the conference held in Brussels from the 3rd to the 5th of December 1984 to mark the twenty-fifth anniversary of the Institute of Archaeology Queen Elisabeth of Belgium at the Hebrew University of Jerusalem (1985)
FB2180.